Population of Lamprosema indicata and Their Parasitoid in Edamame Soybean Plant - Joko Siswanto; Tita Widjayanti; Sri Karindah (University of Brawijaya, 2021)
Soybean Glycine max L. Merrill has a strategic position in food security. Soybean varieties are various, such as edamame or commonly called vegetable soybean. The important edamame pest is L. indicata. This pest has a natural enemy in the form of parasitoids that spread at several altitudes. This study aimed to investigate the L. indicata pest population and their parasitoid in edamame soybean plantations at three different altitudes. In this study conducted at three altitudes namely Purwosari (12 masl), Sebanen (814 masl), and Karangbireuh (1295 masl). At each location consist of one plot (1 Ha) and were made into 4 sub-plots exchanging 10 x10m. Also, the yellow pan trap was installed at 8–57 Day After Planting to collect L. indicata and parasitoid. The results showed that L. indicata was higher in Purwoasri than in other locations. This is due to environmental factors namely temperature. The parasitoid of L. indicata was found in all locations, namely Braconidae family (parasitoid of larvae). While the the paarasitoid were collected in yellow pan trap in all locations i.e. Pteromalidae, Diapriidae, Eulophidae, Mymaridae and Entomacis sp.